In Vitro plant regeneration, antioxidant and antibacterial studies On broccoli, Brassica Oleracea Var. Italica - Farzinebrahimi, R.; Taha, R.M.; Fadainasaband, M.; Mokhtari, S. (2012)
Leaf and shoot tip explant of Brassica oleracea var. italica were inoculated on Murashige and Skoog (MS) basal medium supplemented with various concentrations of (BAP) and (IBA), alone and in combinations to achieve plant regeneration. Subsequently, antioxidant and antibacterial activities were determined from In vitro and In vivo plant parts. The highest mean numbers of shoot was observed on combinations of 1 mg l(-1) and 1.5 mg l(-1) of BAP and IBA, 9.49 and 8.69, respectively. The highest number of shoot produced (11.55) per shoot tip explant was recorded on 2.5 mg l(-1) BAP. In addition, highest percentage of roots (100) and highest mean number of roots produced per leaf explant (8.47) occurred on medium with combination of 1.5 mg l(-1) IBA and BAP by shoot tip explant (4.51). The highest antioxidant activity (70) and 2 mm inhibition zone in antibacterial activity were observed in leaf extract compared to Callus extract.